PENGARUH PENDIDIKAN KESEHATAN MELLAUI PEER GROUP TERHADAP PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) ANAK USIA SEKOLAH (KELAS IV) DI SD NEGERI 6 BATUR: Array (LPPM STIKes Buleleng, 2018)
Introduction: Clean and healthy life is a set of behaviors practiced by students, teachers, and the environment of the school environment based on awareness as a result of learning so that independently able to prevent disease, improve keshatannya and play an active role in realizing a healthy environment. The purpose of this study was to analyze the effect of health education through peer group toward the behavior of clean and healthy life (PHBS) of student (class IV) of elementary school of 6 Batur. Methods: The type of research used pre-experimental with a one-group research design pre-post test design. The data from respondent were collected using an observation sheet bourbonnais. Results: This research used paired t-test with significant level Î±=0,05. The data show the average value of pre 18,23 and the average value of post 24,08. Conclutions: The result of paired t-test p value pre and post (0,000)<Î±, meaning H0 rejected and Ha. it can e conclude that there is effect of health education through peer group toward the behavior of clean and healthy life (PHBS) of student (class IV) of elementary school of 6 Batur